2017
DOI: 10.1123/ijspp.2015-0709
|View full text |Cite
|
Sign up to set email alerts
|

Historical Improvement in Speed Skating Economy

Abstract: Half the improvement in 1500-m speed-skating world records can be explained by technological innovations and the other half by athletic improvement. It is hypothesized that improved skating economy is accountable for much of the athletic improvement. Purpose:To determine skating economy in contemporary athletes and to evaluate the change in economy over the years. years. The association between year and skating economy due to athletic improvement, for the klapskate era, approached significance, suggesting a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For example, previous research showed that top-level cross-country skiers improved performance and work economy, but not VO 2max , from the early preparation phase to the competition phase during a season (Losnegard et al, 2013 ). This is likely explained by the technical complexity of the sport, which is also the case in e.g., speed skating where a recent study suggested that 50% of the improvement in speed skating over the last 50 years is caused by more efficient athletes (even when suits, skates, and ice tracks are accounted for; Noordhof et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous research showed that top-level cross-country skiers improved performance and work economy, but not VO 2max , from the early preparation phase to the competition phase during a season (Losnegard et al, 2013 ). This is likely explained by the technical complexity of the sport, which is also the case in e.g., speed skating where a recent study suggested that 50% of the improvement in speed skating over the last 50 years is caused by more efficient athletes (even when suits, skates, and ice tracks are accounted for; Noordhof et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In long-track speed skating, performance times in the 5000 m and 10,000 m have substantially improved over the last 50 years. Improvements have been explained by technological improvements, such as, indoor ovals, klapskates, aerodynamic suits, improved ice preparation, improving economy and athletic performance [ 51 ]. Another innovation in endurance training is a shift towards more polarised training [ 77 ]; that is, training high volumes in blood lactate concentration zone 1 (low intensity; < 2 mmol) and lower volume of high-intensity (10%–15% in zone 2 and 3; 2–4 and > 4 mmol, respectively) [ 53 ].…”
Section: Strategies For Endurance Trainingmentioning
confidence: 99%